IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS RISET PADA GURU SD DI KECAMATAN KAIRATU - Hutagalung, Berliana; Matitaputty, Jenny Koce (Universitas Pattimura, 2025)
Teaching assistance activities are carried out with the aim of sharing knowledge with teachers in other schools in Maluku. In this activity, there is a research-based learning practice that is applied in the Pattimura University Laboratory school. The stages carried out in this activity are: 1) preparation stage, 2) implementation stage, and 3) evaluation stage. Teaching assistance activities, especially the practice of research-based learning models carried out in Kairatu District, West Seram, went well and had a positive impact on teachers in Kairatu District. Teachers can directly see and practice how to learn by using a research-based learning model in elementary schools. In its implementation, the teachers showed high activity and enthusiasm when carrying out the learning process using the syntax of the research-based learning model. It is hoped that through this activity, teachers will gain knowledge and be able to apply research-based learning models in their respective schools